PARTISIPASI LEMBAGA SWADAYA MASYARAKAT DALAM MENGONTROL PRAKTEK POLITIK UANG PADA PEMILIHAN LANGSUNG KEPALA DAERAH - Solehoddin, Sirajuddin dan (Jurnal Konstitusi, 2010)
To control money politics occuring in the direct election of  local leaders,  there are four forms of participation the non-governmental organizations  in Malang regency can take, namely:  firstly,   making studies and holding discussions and also coalition to unite various parties  in order to eliminate money politic, so a good gorvernance  is created:  secondly, giving political education to the people in order to build their maturity and awareness on the importance of just general election and good governance;  thirdly,  making direct monitoring on the implementation of  direct election of the local  leader and fourthly,  giving pressure to the local government  and the local house of representative to  create good governance consistently and  seriously.